Labour rights as human rights - Alston, Philip (Oxford University Press, 2005)
Are efforts to protect workers' rights compatible with the forces of globalization? How can minimum standards designed to protect labor rights be implemented in a world in which national labor law is more and more at the mercy of international forces beyond its control? The contributors to this volume argue that international agreements and institutions are of central importance if labor rights are to be protected in a globalized economy, exploring some of the options that are open to governments, civil society, and the labor movement in the years ahead